INVESTIGATION OF MINDFUL EMOTION REGULATION - MOHAN RAO, ROSHAN (2018)
As a part of the fulfilment of Final Year Project in Universiti Teknologi PETRONAS, the title chosen was Investigation of mindful emotion regulation. The purpose of this study is to analyse the emotion regulation of the subject once they have been induced to stress and also how mindfulness training would affect the emotion regulation within a time frame of five days. Statistics received from the 2015 Health and Morbidity Survey (NHMS) shows that 4.2million Malaysian adults (age 16 years onwards) and roughly about 29.2 percent suffers from depression. This shows that there is a huge concern that this figures would be able to increase if no proper measurements were taken to overcome this issue. Therefore, the outcome of this experiment should be able to prove that, through mindfulness training, the subject(s) would be able to regulate their emotion despite being induced by stress, which can be objectively accessed through the usage of electroencephalogram (EEG). A part from that, tools such as Brain Electrical Source Activity (BESA) and MATLAB were used for signal pre-processing and feature extraction respectively. On the other hand, the stimulus used were movie clips and arithmetic test. The role of these stimulus are crucial for EEG data acquisition as they were supposed to create emotion and also induced stress based on the respective stimuli. In conclusion, when compared with the frequencies (beta and alpha), beta band provides a better reading as it was able to be more sensitivity in sensing the appropriate emotion based on the stimuli and also regulate the emotion after stress has been induced.